Innovation in Tilapia Cultivation Techniques to Increase Productivity and Quality of Fishery Products in Sidrap - Surianti Anti; Wahyudi Wahyudi; Zennur Rahman Hadi; Devi Permatasari; Muhammad Sahlul; Muh. Ramdansyah (ABDISAINS, 2025)
The training on innovative tilapia farming techniques aims to enhance the productivity and quality of fishery products in Sidenreng Rappang (Sidrap) Regency, which has significant potential in the fisheries sector, particularly tilapia farming. Tilapia farming in Sidrap faces several challenges, including low-quality seeds, suboptimal water quality management, and inefficient feed management. Therefore, this training is designed to provide practical knowledge and skills to the community and students in addressing these issues. The training covers innovative techniques such as efficient pond preparation, optimal water quality management, selection and provision of natural feed, and handling of fish seeds to improve resilience to changing environmental conditions. The training method involves both theoretical and hands-on practice at the Education Pond of Muhammadiyah University of Sidenreng Rappang (UMS Rappang). It is expected that this training will provide concrete solutions to improve the quality of tilapia farming and encourage the creation of a sustainable farming model in Sidrap, which will increase productivity and the welfare of fish farmers in the region.